Adaption of a Muslim Religiosity Scale for Use with Four Different Faith Communities in Malaysia - Krauss, Steven Eric; Hamzah, Azimi; Idris, Fazila (2007)
Though many religiosity scales originally developed for use with Judeo-Christian populations have been adaptedfor use with Muslim populations (Spilka et al. 2003), no known scales developed for Muslims have been adapted for use by non-Muslim adherents. In an attempt to measure religiosity of Malaysian youth across four faith communities (Muslims, Hindus, Buddhists and Christians), researchers required the use of an instrument that would be universally applicable and accepted. The Religious Personality subscale of the Muslim Religiosity-Personality Inventory (MRPI)(Krauss et al. 2006) was selected. The current paper set out to report on the process and results of scale adaptation. Psychometric results indicate that the scale is reli able, valid and relevant for use with multiple faith groups. Concerns about social desirability in relation to the religiosity scale are also considered. The study also highlights the needfor more formal research on religiosity among non-Muslim faith groups in Malaysia as most of the formal research to date has been conducted on Muslim Malays.